2021
DOI: 10.21037/atm-20-3451
|View full text |Cite
|
Sign up to set email alerts
|

Pain assessment in clinical trials: a narrative review

Abstract: Pain is a symptom measured in many clinical trials. For pain as an outcome domain, trialists need to choose adequate outcome measure(s), as there are myriad outcome measures for pain to choose from. To ensure consistency and uniformity in clinical trials and systematic reviews, core outcome sets (COS) have been defined; COS includes a predefined minimal list of core outcomes that should be measured within a trial, to ensure their consistency and comparability. COS is defined via consensus procedure, which incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Pain, especially chronic pain, is one of the biggest public health problems in our society [ 1 ]. A survey by the National Center for Health Statistics found that low back pain (LBP), migraine or severe headache, and joint pain were the most common types of chronic pain in clinical practice [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pain, especially chronic pain, is one of the biggest public health problems in our society [ 1 ]. A survey by the National Center for Health Statistics found that low back pain (LBP), migraine or severe headache, and joint pain were the most common types of chronic pain in clinical practice [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because pain is a subjective individual experience, self-reported pain intensity is considered the gold standard for evaluating pain in clinical situations [ 1 , 2 ]. However, the clinical pain measure always needs careful evaluation and a skillful clinician to guide [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation